Karakteristik Mushaf Kagungan-Dalem Masjid Agung Kadipaten Pakualaman - Febriyanto, Muhammad Bagus; Azami, Hadiana Trendi (SUHUF, 2023)
Mosque collection. As a new discovery, these manuscripts have not been previously disclosed to the public. This research is important given the minimal attention that Qur’anic manuscript studies in the Pakualaman Duchy have received from researchers, thereby prompting further investigation. The method employed is qualitative-descriptive research conducted in three stages. The first step involves manuscript inventory, the second step includes manuscript description, and the third step comprises analysis. A codicological approach is used to discover the characteristics of the manuscripts, while the Qur’anic sciences are applied to analyze the script (rasm), recitations (qira'at), and Tajweed signs. The results show that the six ancient manuscripts of the Pakualaman Grand Mosque predominantly use the imla'i rasm with various qira'at of 'Asim from the Hafs transmission. Two manuscripts contain a type of illumination called “wedana renggan” with simple ornamentation. The color variants and forms of illumination of the Pakualaman Grand Mosque manuscripts tend to be simpler and serve a decorative purpose.